2006
DOI: 10.1158/1078-0432.ccr-05-1601
|View full text |Cite
|
Sign up to set email alerts
|

CpG Island M`ethylation Status in Gastric Carcinoma with and without Infection of Epstein-Barr Virus

Abstract: Purpose: EBV-associated gastric carcinoma shows global CpG island methylation of the promoter region of various cancer-related genes. To further clarify the significance of CpG island methylator phenotype (CIMP) status in gastric carcinoma, we investigated methylation profile and clinicopathologic features including overall survival in four subgroups defined by EBV infection and CIMP status: EBV-associated gastric carcinoma and EBV-negative/CIMP-high (H), EBV-intermediate (I), and EBV-negative (N) gastric carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(146 citation statements)
references
References 23 publications
7
132
0
1
Order By: Relevance
“…In several studies, many authors have indicated the existence of a mechanistic linkage between DNA methylation and infection agents. 11,22,[38][39][40][41] This observation has prompted us to suggest the analysis of the relation between JCV infection and the heritable loss related to promoter hypermethylation. To our knowledge, no study has assessed the relationship between JCV-associated gastric carcinomas and the methylation of tumor-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, many authors have indicated the existence of a mechanistic linkage between DNA methylation and infection agents. 11,22,[38][39][40][41] This observation has prompted us to suggest the analysis of the relation between JCV infection and the heritable loss related to promoter hypermethylation. To our knowledge, no study has assessed the relationship between JCV-associated gastric carcinomas and the methylation of tumor-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23]30,32,33 However, these previous studies used a small number of CpG island loci by MSP. In our study analyzing 27 CpG island loci by MethyLight, which overcomes some variability problems of MSP, the average MI of EBV-positive GCs and MSI-positive GCs was 0.98 and 0.48, respectively, whereas that of GCs negative for both was 0.37.…”
Section: Methylation In Gc Was Revealed For the First Time In Thismentioning
confidence: 99%
“…The current study found CIMP-H in 22% of GCs using four MINT genes MINT1, MINT2, MINT25 and MINT31 . In other studies, CIMP was de ned by the DNA methylation status of tumor-related genes, rather than MINT genes [18][19][20] -methylguanine DNAmethyltransferase was linked to the responsiveness of brain tumors to alkylating agents. These positive relationships between the DNA methylation of cancer-related genes and therapeutic ef cacy might be implicated in the longer survival time of GC patients with CIMP-H. Our data shows that the survival time of GC patients with CIMP-H is likely to be longer than those with CIMP-L/CIMP-N GCs, but no statistical differences were observed in survival time among patients with different CIMP status.…”
Section: Discussionmentioning
confidence: 99%